Weak sunlight-driven mass toluene combustion through scalable Cu doped CeO2 microspheres. (15th April 2021) - Shi, Chengcheng; Yuan, Dachao; Ma, Luping; Fu, Guangsheng; Wang, Shufang; Li, Yaguang
Abstract: Sunlight-driven toluene elimination system faces the problems of low reaction rate, secondary pollution, and especially tricky to large-scale production. In this work, we used a PVP assisted spray drying method to synthesize Cu doped CeO2 microspheres with the merits of zero waste water and solids discharge, kilogram level yield, uniform dispersion of Cu, and high toluene combustion activity. Further, a new photothermal device was constructed to heat catalysts to 295 °C under one standard sunlight irradiation. As a result, the new photothermal device supported Cu doped CeO2 microspheres showed a full oxidation of toluene at the rate of 59.82 mmol g −1 h −1 under 1 sun irradiation, 150 times higher than the advanced sunlight-driven toluene elimination. An industrial demonstration of this new system was developed, and this system was able to completely deal with 22.2 m 3  h −1 of exhaust with the toluene concentration of 1–10, 000 ppm under 1 m 2 of outdoor sunlight irradiation in the daytime of winter, showing the potential on industrial applications.